# Help in proving abs(abs(x)-abs(y))<=abs(x-y)

1. Apr 2, 2014

### lilli-baba

1. The problem statement, all variables and given/known data
already proved abs(x)-abs(y)≤abs(x-y)
I just don't know how to prove it
2. Relevant equations

3. The attempt at a solution
we have :abs(x)-abs(y)≤abs(x-y)
abs(x)-abs(y)/abs(x-y)≤1 / abs(x-y) is diff than 0

proving abs(abs(x)-abs(y))/abs(x-y))≤1 :abs(x-y)diff than 0 then...
abs(abs(x)-abs(y)/abs(x-y))≤1 / abs(x-y)=abs(abs(x-y))

a<=abs(a)
a=abs(x)-abs(y)/abs(x-y)) :a≤1
abs(x)-abs(y)/abs(x-y))≤abs(abs(x)-abs(y)/abs(x-y))....
can't continue from here...I don't think this is the right way to do it
please any help.

2. Apr 2, 2014

### MathematicalPhysicist

Well,

from |x| <= |x-y|+|y|
and |y| <= |y-x|+|x|

So you have: |x|-|y| , |y|-|x| <= |x-y|
Then because ||x|-|y|| equals one of them, what can you infer?

3. Apr 2, 2014

### HallsofIvy

Staff Emeritus
I would do this in four cases:
1) x> 0, y> 0
2) x> 0, y< 0
3) x< 0, y> 0
4) x< 0, y< 0

And each case would have two "subcases"
a) |x|> |y|
b) |x|< |y|

4. Apr 3, 2014

### Curious3141

The way I did it was to take $\displaystyle ||x| - |y||.||x| + |y||$ and simplify it algebraically, ending up with $\displaystyle ||x| - |y|| = |x-y|.|\frac{x+y}{|x| + |y|}|$.

It should be quite trivial to observe that the factor on the right is always positive, and has a maximum value of 1, and that only occurs when x and y are of the same sign.

Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted